Stock Investment Training to Achieve Financial Freedom in The Youth Community - Dewita Puspawati; Widowati Dian Permatasari; Novel Idris Abas; Alfandi Rico Yohanda (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
In modern society, investment has become an important necessity for the future. However, currently there are still many young people who still lack interest in investing because of the lack of programs that can improve their financial literacy. One of them is the Youth Community in Badung Regency, Bali. In this community, the younger generation/teenagers are still not interested in investing. This is due to the lack of socialization about the ease of investing in the present. This community service aims to increase knowledge and information about investment, increase the motivation youth community members to be more productive during the pandemic, and a means of empowering the younger generation to be able to manage finances and form financial independence through positive and productive activities.